2014
DOI: 10.5306/wjco.v5.i3.393
|View full text |Cite
|
Sign up to set email alerts
|

Toremifene in the treatment of breast cancer

Abstract: Core tip: Toremifene is safe and effective in the treatment of breast cancer. Toremifene and tamoxifen are equivalently effective in the treatment of breast cancer, although some studies show an advantage for toremifene. Safety and tolerability is also broadly equivalent, although toremifene may cause fewer uterine neoplasms, serious vascular adverse events and has a more beneficial effect on plasma lipids than does tamoxifen.Mustonen MVJ, Pyrhönen S, Kellokumpu-Lehtinen PL. Toremifene in the treatment of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 61 publications
(96 reference statements)
2
19
0
Order By: Relevance
“…The commonly used dose of toremifene in humans for treating ER ϩ breast cancer is 60 mg daily (16,39). However, several clinical studies with higher toremifene doses (200 and 240 mg/day) in humans showed no significant increase in toxic side effects compared to the standard dose of 60 mg toremifene daily (40)(41)(42)(43)(44)(45). The latter studies confirm that the toremifene dose used in this study (3 mg/kg/day) is achievable in humans.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The commonly used dose of toremifene in humans for treating ER ϩ breast cancer is 60 mg daily (16,39). However, several clinical studies with higher toremifene doses (200 and 240 mg/day) in humans showed no significant increase in toxic side effects compared to the standard dose of 60 mg toremifene daily (40)(41)(42)(43)(44)(45). The latter studies confirm that the toremifene dose used in this study (3 mg/kg/day) is achievable in humans.…”
supporting
confidence: 70%
“…In addition, an elevated risk of thromboembolic events, endometrial cancer (higher for tamoxifen treatment), and a prolongation of the QT interval is noticed in some cases when using ER modulators such as tamoxifen and toremifene. Besides these adverse side effects, tamoxifen and toremifene have positive effects on serum lipid levels (decreased cholesterol) and bone mineral density (16,44,45).…”
mentioning
confidence: 99%
“…Despite the progress in combined modality therapies, the long-term outcome of patients with breast cancer is far from satisfactory [2]. This outcome is mainly attributed to the induction and progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Toremifene ( Figure 1B) is similar to TAM in clinical activity, efficacy and tolerability, and is cross-resistant to TAM. It causes less vascular and endometrial adverse effects than TAM, but has less favorable actions on bone and lipids levels [30] . Also in patients with metastatic BC, the results of TAM and toremifene therapy did not differ significantly, and the latter represents a reliable alternative to TAM in menopausal women [31] .…”
Section: Down-regulatorsmentioning
confidence: 99%